The impact of perineal massage during pregnancy on perineal laceration during childbirth and postpartum: A randomized clinical trial study - Shahoei, Roonak; Hashemi-Nasab, Lila; Gaderkhani, Golbahar; Zaheri, Farzaneh; Shahoei, Faranak (Chronic Diseases Journal, 2018)
BACKGROUND: This study was aimed to investigate the effect of perineal massage during pregnancy on perineal pain and lacerations. METHODS: This randomized clinical trial study was conducted at Besat Hospital of Sanandaj, Iran, from June 2014 to July 2015, on 115 women. Subjects in the intervention group practiced a daily 8-minute perineal massage with olive oil, starting from the 34th week of gestation until delivery. A questionnaire, made by researchers, was used to collect data through interviews and observations as well as reading the women’s health files. The collected data was analyzed using SPSS software. The descriptive results were reported in terms of frequencies, means and standard deviations (SD). RESULTS: The incidence of episiotomy was 53.33% and 57.33% in interventional and control groups, respectively, reflecting the significant difference (P < 0.050). In the interventional group, the frequency of first and second-degree and urethra tears was 81.82%, 9.09%, and 9.09%, respectively. The frequency of the first and second-degree, urethra and vestibule tears was 72.23%, 11.11%, and 16.66%, respectively, in control group. Comparing the degrees of pain between two groups revealed the significant difference in severity of pain at 3 days, 10 days and 3 months after childbirth (P < 0.001). CONCLUSION: Antenatal perineal massage has a significant effect on the incidence of intact perineum, episiotomy and postnatal perineal pain.